The reliability and validity of the International Spinal Cord Injury Quality of Life Basic Data set in people with spinal cord injuries from a middle-income country: a psychometric study of the Thai version - Sintip Pattanakuhar (2020)
© 2020, The Author(s), under exclusive licence to International Spinal Cord Society. Study Design: A cross-sectional study. Objectives: To examine psychometric properties, including internal consistency, construct validity, and test–retest reliability, of the Thai version of the International Spinal Cord Injury (ISCI) Quality of Life Basic Data Set (QoL-BDS). Setting: Outpatient rehabilitation clinic, urodynamic clinic, and rehabilitation ward at Maharaj Nakorn Chiang Mai Hospital. Methods: Participants were assigned to complete two assessment tools, the Thai version of QoL-BDS which consisted of three single items on satisfaction with life as a whole, physical health and psychological health, and the Thai version of the World Health Organization Quality of Life instrument (WHOQOL-BREF) completed by face to face interview. After 2 weeks, the participants were evaluated the QoL-BDS again via telephone interviewing to assess test–retest reliability. Results: One hundred and thirty people with spinal cord injury (SCI) were included in the study. Of all participants, 103 people had a traumatic SCI. The mean (SD) age was 43.0 (13.1) years and the median (IQR) time after SCI was 7.5 (1–14) years. The Thai version of QoL-BDS had good internal consistency (Cronbach’s alpha = 0.89), fair to good construct validity (Spearman’s rank correlation coefficient of 0.43–0.57, p < 0.01) and good to excellent test–retest reliability (Intraclass correlation coefficient of 0.73–0.86). Conclusions: The Thai version of QoL-BDS had acceptable psychometric properties. As it is concise, QoL-BDS should be encouraged in healthcare providers to investigate QoL in people with SCI, especially in middle-income countries.